Quantum percolation in granular metals - Feigel'man, M V; Ioselevich, A S; Skvortsov, M A (Physical review letters, 2004)
Theory of quantum corrections to conductivity of granular metal films is developed for the realistic case of large randomly distributed tunnel conductances. Quantum fluctuations of intergrain voltages (at energies E much below the bare charging energy scale E(C)) suppress the mean conductance g (E) much more strongly than its standard deviation sigma(E). At sufficiently low energies E(*) any distribution becomes broad, with sigma(E(*)) approximately g (E(*)), leading to strong local fluctuations of the tunneling density of states. The percolative nature of the metal-insulator transition is established by a combination of analytic and numerical analysis of the matrix renormalization group equations.